2013
DOI: 10.1136/amiajnl-2012-001055
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and preventing wrong-patient electronic orders: a randomized controlled trial

Abstract: Wrong-patient electronic orders occur frequently with computerized provider order entry systems, and electronic interventions can reduce the risk of these errors occurring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
167
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(172 citation statements)
references
References 21 publications
3
167
1
1
Order By: Relevance
“…Assuming a baseline error rate of 60 RAR events per 100 000 orders, 13 and assuming an estimated effect size that was based on previous wrong-patient error research, 6 our study duration of 1 year of control data collection and 1 year of intervention data collection provided .90% power to detect a 40% reduction in the odds of an RAR event. The effect size (ie, 40% reduction in RAR events) that we used for this calculation is taken from the results of a randomized controlled trial that evaluated the efficacy of an improved patient identification system for preventing wrong-patient electronic orders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming a baseline error rate of 60 RAR events per 100 000 orders, 13 and assuming an estimated effect size that was based on previous wrong-patient error research, 6 our study duration of 1 year of control data collection and 1 year of intervention data collection provided .90% power to detect a 40% reduction in the odds of an RAR event. The effect size (ie, 40% reduction in RAR events) that we used for this calculation is taken from the results of a randomized controlled trial that evaluated the efficacy of an improved patient identification system for preventing wrong-patient electronic orders.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggested that 76.2% of RAR events represent wrong-patient errors. 6 RAR events are near-miss errors, self-caught by the clinician before they reach the patient. The Eunice Kennedy Shriver National Institute of Child Health and Human Development defines near-miss errors as "those errors that do not result in patient harm due to chance or timely interventions."…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple safety publications have addressed computerized physician order entry (CPOE) associated gains in safety (eliminating prescriber handwriting errors), as well as its unintended consequences due to screen arrangement, data entry errors (weight in pounds instead of kilograms), and wrong-patient orders [45,46]. The ED medication safety team identified multiple local CPOE problems, such as the appearance of a medication on the ordering screen and trade/generic name confusion.…”
Section: Multidisciplinary Teamworkmentioning
confidence: 99%
“…Wrong patient errors which have the potential to lead to diagnostic errors have received attention. In one study, a health IT safety measure, known as the Retract-and-Reorder measure, was introduced as a tool hospitals can utilize to examine "near misses" of wrong patient error so that subsequent preventive action could be taken [25].…”
Section: Detecting Safety Riskmentioning
confidence: 99%